Adhesive failure of grooved tool in milling of 3Cr-1Mo-1/4V steel. (16th February 2012) - Tan, Guangyu; Liu, Guangjun; Li, Guanghui
The adhesive failure of an uncoated cemented carbide tool was investigated in face milling of 3Cr-1Mo-1/4V stainless steel. The milling force and milling temperature were measured. The temperature field, stress field and thermo-mechanical coupled fields were analysed by the finite element method. The adhesion phenomenon between materials of the workpiece and the tool were observed. Analysis of energy spectrum was performed to evaluate the adhesion between the tool and chips. The failure mechanism at the end of tool life was investigated in detail using scanning electron microscope (SEM) and correlated to the chemical and mechanical properties of the tool.